The Communication Forum of Batang Coal-Fired Power Station Used for the Conflict Resolution Across the Countryside (Case Study Socialization of Batang Coal-Fired Power Station in the Karanggeneng Village, Kandeman Subdistrict, Batang District) - Rizki Kurnia Yuniasti; Triyono Lukmantoro; Turnomo Rahardjo; Wiwid Noor Rakhmad (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2015)
Coal-fired power station development planned by PT Bhimasena Power Indonesia and The Batang District Goverment is one of the innovation for the Karanggeneng civilization, Kandeman Subdistrict of Batang District triggered some conflicts so that development project has been delayed. The research purpose is to describe the socialization and how the Communication Forum of Batang Coal-Fired Power Station can solve the conflict. The research is descriptive qualitative approach to understanding the perspective of interpretive while research method used is a case study method. The research theories are Uncertainty Reduction Theory, Diffussion of Inovation Theory, Triangle of Conflict Theory, The Principle of Negotation theory, and The Convergence of Model Communication. This research result indicates that the socialization of coal-fired power Batang done through the formal and informal sides. The obstacles in this socialization are late socialization, uncertainty of information because the the other hand informations, social estrangement (social estrangement to be two namely pro and contra for Batang coal-fired power station) Batang coal-fired power station development and conflicts namely compensation land and social compensation. The communication forum of Batang coal-fired power station in the Karanggeneng Village have not been able to resolve the conflict in the Karanggeneng village. The communication forum Batang coal-fired power station experienced divergence at the time of the negotiation process due to the absence of mutual understanding. Negotiations containing the equivalent communication, openness information and mutual understanding is the communication models which is proper for the conflict resolution with The Convergence Communication Models.